2009
DOI: 10.1007/s11671-009-9498-0
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Semiconductor Nanowires with Neurons and Their Interfacial Structure

Abstract: We report on the compatibility of various nanowires with hippocampal neurons and the structural study of the neuron–nanowire interface. Si, Ge, SiGe, and GaN nanowires are compatible with hippocampal neurons due to their native oxide, but ZnO nanowires are toxic to neuron due to a release of Zn ion. The interfaces of fixed Si nanowire and hippocampal neuron, cross-sectional samples, were prepared by focused ion beam and observed by transmission electron microscopy. The results showed that the processes of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The research activity on semiconducting nanowires ͑NWs͒ is one of the most rapidly developing area in material science due the variety of important applications which, in the last years, has been envisaged in the fields of electronics, 1 optoelectronics, 2 nanomedicine, 3 and bioelectronics. 4 Due to their compatibility with the existing Si-based microelectronics, Si, 5 but also Ge and SiGe NWs have been the subject of intense experimental [6][7][8][9][10][11] and theoretical [12][13][14][15][16][17][18][19][20][21][22][23] investigations.…”
mentioning
confidence: 99%
“…The research activity on semiconducting nanowires ͑NWs͒ is one of the most rapidly developing area in material science due the variety of important applications which, in the last years, has been envisaged in the fields of electronics, 1 optoelectronics, 2 nanomedicine, 3 and bioelectronics. 4 Due to their compatibility with the existing Si-based microelectronics, Si, 5 but also Ge and SiGe NWs have been the subject of intense experimental [6][7][8][9][10][11] and theoretical [12][13][14][15][16][17][18][19][20][21][22][23] investigations.…”
mentioning
confidence: 99%
“…As CVDgrown Si nanowires have high-aspect-ratios (<10 3 ) and are sufficiently rigid to be mechanically manipulated, their nanometer scale diameters and high-aspect-ratios allow them to access the interiors of living cells without an external force for penetration. Previous studies have shown that CVD-grown vertical nanowires spontaneously penetrate the cell membrane when cells are placed on top of the nanowires [26][27][28][29][30][31] . The biocompatibility of small diameter nanowires is a critical element for the in situ study of cellular processes of living cells 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our previous study indicated that Si nanowires are bio-compatible to excitable cells (hippocampal neurons) and are thus safe for interfacing [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Based on the findings of previous studies [26,27], the length (3 to 4 μm) and the diameter (60 to 100 nm) of the nanowires were set to optimum cell interfacing conditions.…”
Section: Methodsmentioning
confidence: 99%